Arthroscopic Fixation of ACL and PCL Avulsion with Medial Tibial Plateau Fracture in a Patient with Osteogenesis Imperfecta - Gunatilake, Tessanya; Smith, Joel (Archives of Clinical and Medical Case Reports, 2025)
Osteogenesis imperfecta is a rare genetic connective tissue disorder resulting in bone fragility. We present a unique case of an avulsion of both the anterior cruciate and posterior cruciate ligaments, along with a medial tibial plateau fracture in a patient with osteogenesis imperfecta and vascular complications. Our case highlights the challenges of managing traumatic knee injuries complicated by bone fragility and vascular risks, underscoring the importance of a multidisciplinary approach for effective fixation.